Hypertension and heart failure with preserved ejection fraction: position paper by the European Society of Hypertension. Issue 8 (August 2021) - Kasiakogias, Alexandros; Rosei, Enrico Agabiti; Camafort, Miguel; Ehret, Georg; Faconti, Luca; Ferreira, João Pedro; Brguljan, Jana; Januszewicz, Andrzej; Kahan, Thomas; Manolis, Athanasios; Tsioufis, Konstantinos; Weber, Thomas; et al.
Abstract : N/A: Hypertension constitutes a major risk factor for heart failure with preserved ejection fraction (HFpEF). HFpEF is a prevalent clinical syndrome with increased cardiovascular morbidity and mortality. Specific guideline-directed medical therapy (GDMT) for HFpEF is not established due to lack of positive outcome data from randomized controlled trials (RCTs) and limitations of available studies. Although available evidence is limited, control of blood pressure (BP) is widely regarded as central to the prevention and clinical care in HFpEF. Thus, in current guidelines including the 2018 European Society of Cardiology (ESC) and European Society of Hypertension (ESH) Guidelines, blockade of the renin-angiotensin system (RAS) with either angiotensin-converting enzyme inhibitors or angiotensin receptor blockers provides the backbone of BP-lowering therapy in hypertensive patients. Although superiority of RAS blockers has not been clearly shown in dedicated RCTs designed for HFpEF, we propose that this core drug treatment strategy is also applicable for hypertensive patients with HFpEF with the addition of some modifications. The latter apply to the use of spironolactone apart from the treatment of resistant hypertension and the use of the angiotensin receptor neprilysin inhibitor. In addition, novel agents such as sodium-glucose co-transporter-2 inhibitors, currently already indicated for high-risk patients with diabetes to reduce heart failure hospitalizations, and finerenone represent promising therapies and results from ongoing RCTs are eagerly awaited. The development of an effective and practical classification of HFpEF phenotypes and GDMT through dedicated high-quality RCTs are major unmet needs in hypertension research and calls for action.